Antidiabetic activity and HPLC-PDA profile of herbal formulation in patients with type 2 diabetes: a randomized controlled trial (Indian Journal of Traditional Knowledge (IJTK), 2025)
The use of herbal medicines is widely common to control blood sugar. This study was performed in the way of a triple-blind clinical trial to study the effects of standardized herbal formulation (Eryngium billardieri, Urtica dioica, Trigonella foenum-graecum, Abelmoschus esculentus, Cinnamomum zeylanicum and Rosa canina) on fasting plasma glucose and Hemoglobin A1c. This placebo controlled trial was performed on 88 patients with type 2 diabetes. Patients were followed up at the beginning and after the end of the 3-months for assessment of fasting plasma glucose (FPG), Hb-A1c, and body mass index (BMI). The intervention group received 200 mg/day herbal formulation extract capsules and the control group received placebo. To standardize the herbal formulation, RP-HPLC-PDA was used. The amount of FPG and Hb-A1c were significantly reduced (p=0.001) in the intervention group compared to the control group; FPG difference=53.20 (95% CI: 34.51, 71.89; p=0.001); Hb-A1c difference=1.60 (95% CI: 1.15, 2.05; p=0.001). It is noteworthy that, no adverse events were observed during the study. According to HPLC analysis, the amount of benzoic acid, rutin, naringenin, gallic acid, caffeic acid, resveratrol, and apigenin (609.6, 265.4, 220.2, 188.4, 164, 109, 29.9 μg/capsule, respectively) was specified in the herbal formulation. The results of this trial indicated that standardized herbal formulation can be effective in reducing FPG and Hb-A1c among patients with type 2 diabetes. It may be used as a dietary or medical supplement to control blood glucose. However, further investigation is suggested.